Focus on One or More? Cultural Similarities and Differences in How Parents Talk About Social Events to Preschool Children - Kuwabara, Megumi; Smith, Linda B. (Frontiers in Psychology, 2022)
How parents talk about social events shapes their children's understanding of the social world and themselves. In this study, we show that parents in a society that more strongly values individualism (the United States) and one that more strongly values collectivism (Japan) differ in how they talk about negative social events, but not positive ones. An animal puppet show presented positive social events (e.g., giving a gift) and negative social events (e.g., knocking over another puppet’s block tower). All shows contained two puppets, an actor and a recipient of the event. We asked parents to talk to their three- and four-years old children about these events. 26 parent-child dyads from the U.S. (M=41.92 months) and Japan (M=42.77 months) participated. The principal dependent measure was how much parent talk referred to the actor of each type of social event. There were no cultural differences observed in positive events - both the U.S. and Japanese parents discussed actors more than recipients. However, there were cultural differences observed in negative events - the U.S parents talked mostly about the actor but Japanese parents talked equally about the actor and the recipient of the event. The potential influences of these differences on early cognitive and social development are discussed.